Toxicity study of insecticide formulations on stingless bee Heterotrigona itama (Cockerell) (Apidae: Meliponini) - Siti Asma Samsudin,; Nur Azura Adam,; Norida Mazlan,; Puteri Edaroyati Megat Wahab,; Wan Nur Asiah Wan Mohd Adnan,; Mohamad Syukri Tan Shilan, (Penerbit Universiti Kebangsaan Malaysia, 2024)
Application of insecticides is a must in crop cultivation to produce high quality product in market. The excess application of insecticides is a major concern as it could harm insect pollinators, which results in broken colonies of pollinator especially stingless bee. This study aimed to determine the toxicity level of selected insecticides toward stingless bee populations. The bioassay on the toxicity level that cause mortality on stingless bee population, Heterotrigona itama population was assessed with five common insecticides used in rock melon cultivation, namely deltamethrin, cypermethrin, imidacloprid, abamectin and malathion. Imidacloprid exhibited the highest toxicity causing 50% mortality after 24 hours with a concentration as low as 57.53ppm. The insecticide with the lowest toxicity on Heterotrigona itama was malathion, where a high concentration of 500.76 ppm resulted in 50% mortality after 24 hours. Results reaffirmed that the use of highly toxic insecticides are detrimental to populations of pollinators.